Surgical Outcome in Focal Cortical Dysplasia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
The predictors of surgical outcome and relevance of pathological severity were determined in 166 consecutive patients with intractable epilepsy and focal cortical dysplasias treated surgically at Konkuk University Medical Center, and National University Hospital, Seoul, Korea.